Optimalisasi Generasi Muda Siaga Melalui Pelatihan Bantuan Hidup Dasar (BHD) Berbasis Demonstrasi: Optimizing Youth Readiness through Demonstration-Based Basic Life Support (BLS) Training - Widayati, Dhina; Rachmania, Diana; Setyorini, Dwi (Chakra Brahmanda Lentera Institute, 2025)
One type of emergency problem that can cause sudden death is usually caused by cardiac arrest. Basic life support training provided to PMR cadres can improve the knowledge and skills of the younger generation in providing basic life support, especially in cases of cardiac arrest. The purpose of this community service activity is to optimize the role of PMR cadres so that they are able to educate about basic life support in cases of cardiac arrest through demonstrations and community service participants learn about how to provide basic life support in cases of cardiac arrest. The method of implementing this activity is carried out through lecture and demonstration methods involving 6 PMR cadres and 20 student participants from SMK YP 17 Pare. This activity was carried out on April 10-12, 2025. The implementation of the activity consisted of 2 sessions. The first session was empowering PMR cadres through cadre training activities on basic life support in cases of cardiac arrest and the second session was delivering material by trained cadres which was delivered to community service participants. The results of this community service activity were that trained cadres were able to deliver the material well, there was an increase in knowledge and ability of participants in providing basic life support in cases of cardiac arrest after demonstration education was carried out by trained cadres. Education through empowerment of cadres as a way to optimize the role of the younger generation can improve students' understanding of basic life support in cardiac arrest. As agents of change and possessing significant social influence, the younger generation is expected to be able to educate more people through creative and relevant methods.